COMPARING THE METHODS OF AFRICAN SWINE FEVER EPIZOOTOLOGICAL MONITORING - Behas, V. L.; Romanyshyna, T. O.; Rybachuk, Zh. V.; Pins'kyi, O. V. (Scientific Progress & Innovations, 2019)
The monitoring of the situation concerning African swine fever (ASF) in Ukraine is becoming less effective. The systems of monitoring ASF play an important role in the system of animal disease control, since they allow to get the necessary data and to respond quickly to the situation. Certainly, not all the strategies of monitoring are suitable for Ukraine because of its natural geographic and social-economic peculiarities. The analysis of epizootic data on ASF for the period of 2012–2019 in Ukraine was made, using Internetbased resources (www.asf.vet.ua, http://www.asfld.vet.ua, http://www.asfld.vet.ua/index.php/view-data.), we found out that the highest rate of the disease occurred in 2017, as in 2018 and 2019 the number of the disease cases decreased due to domestic animals. However, this information may not reflect the situation concerning ASF in Ukraine fully, taking into account the fact that the areas of some regions in accordance with the data of the State Emergency Anti-Epizootic Commission are disease-free. There is an increase of ASF cases in wildlife and the number of infected objects. In our opinion the additional passive monitoring at this stage is necessary. This is due to the fact that in Ukraine, the human factor influences considerably the measures of fighting ASF. The method of monitoring pork carcasses which are delivered for selling through the laboratories of veterinary-sanitary expert examination from households was tested, and this method enabled to get the information on epizootic situation concerning ASF in certain areas without significant interfering in the process. 2844 samples were selected, which were investigated in PCR at ASF. But this method has also its drawbacks: in case of getting positive results of testing on ASF, the products had already been sold, and it was impossible to conduct the liquidation measures. But it was possible to compare the results of the State Emergency Anti-Epizootic Commission with the results of examining carcasses. The information resource “Stop ASF” informs the specialists of veterinary medicine, owners of pigs, pig farms, farmers, hunters, butchers, cargo carriers, and ordinary citizens about the state and degree of ASF threat in Ukraine and in the world, the peculiarities of its identifying, preventing, and eliminating in case of its emergence and familiarizing with the best practices in organizing anti-epizootic measures. But at this stage its possibilities are insufficient. It is necessary to continuously conduct additional passive monitoring of ASF in the laboratories of veterinary-sanitary expert examination on the market, by PCR analysis of samples taken from pig carcasses for the presence of ASF virus genome. The measures to overcome ASF should be developed taking into account the results of all monitoring sources.